Efektifitas Konseling Seksual untuk Keharmonisan Keluarga Pasien Penyakit Ginjal Kronik Usia Produktif yang Menjalani Hemodialisis (Journal of Telenursing (JOTING), 2023)
The purpose of this study was to determine the effectiveness of sexual counseling on family harmony in productive age chronic kidney disease patients undergoing hemodialysis. This type of quantitative research uses a quasi-experimental study with a control group design where researchers provide sexual counseling interventions for family harmony in productive age chronic kidney disease patients undergoing hemodialysis. The results showed a p-value = 0.001 (p